Genetic Characterization of Nipah Virus, Bangladesh, 2004 - Harcourt, Brian H. (Centers for Disease Control and Prevention, 2005)
Until 2004, identification of Nipah virus (NV)-like outbreaks in Bangladesh was based on serology. We describe the genetic characterization of a new strain of NV isolated during outbreaks in Bangladesh (NV-B) in 2004, which confirms that NV was the etiologic agent responsible for these outbreaks.